Single-Domain Antibodies As Therapeutics against Human Viral Diseases - Wu, Yanling; Jiang, Shibo; Ying, Tianlei (Frontiers in Immunology, 2017)
In full-size formats, monoclonal antibodies (mAbs) have been highly successful as therapeutics against cancer and immune diseases. However, their large size leads to inaccessibility of some epitopes and relatively high production costs. As an alternative, single-domain antibodies (sdAbs) offer special advantages compared to full-size antibodies, including smaller size, larger number of accessible epitopes, relatively low production costs and improved robustness. Currently, sdAbs are being developed against a number of viruses, including human immunodeficiency virus-1 (HIV-1), influenza viruses, hepatitis C virus (HCV), respiratory syncytial virus (RSV) and enteric viruses. Although sdAbs are very potent inhibitors of viral infections, no sdAbs have been approved for clinical use against virial infection or any other diseases. In this review, we discuss the current state of research on sdAbs against viruses and their potential as therapeutics against human viral diseases.